Research on the Impact of Different Corporate Cultures on Corporate Social Responsibility - Mao, Weiqing; Qi, Ying; Zheng, Wenshan (Economics & Management Review, 2020)
Corporate culture plays a guiding, restricting, stimulating, cohesive, and coordinating role in business management. Different corporate culture atmospheres can affect the choice of corporate social responsibility. This article adopts a questionnaire for 317 companies in 7 cities in the Yangtze River Delta region Investigate and analyze four different types of corporate culture: clans, hierarchies, markets, and innovative corporate cultures on corporate social responsibility. The results show that: clan corporate culture has the most significant impact on CSR, and hierarchal corporate culture Only local impact on CSR is significant, and market-oriented corporate culture has no significant impact on CSR. In addition, the impact of innovative corporate culture on CSR is complex. This study has certain conscious behaviors and mechanism construction for social responsibility of different types of enterprises. Guiding significance.